(untitled) (Journal of Economic Research & Business Administration, 2019)
This article is devoted to a new financial instrument, like cryptocurrency. This financial instrument gradually captures world markets. Definitely, simple money is replaced by digital money with the development of information technology. The new instrument does not have a centralized system of control and is protected from counterfeit, which may favorably contribute to the development of this currency in the future. The influence of modern information and technological innovations characterizes not only the functioning of the main financial processes, but also all other production processes, while being not only a consequence of accelerating the dynamics of economic progress, but also a new factor in the variability of economic systems. The ability to remotely combine computers into one network to solve specific problems has become the basic idea for creating a new type of electronic money with a modern information system. The article reveals the main points related to cryptocurrency and shows the factors affecting its value. Considering that each monetary currency has a certain cost, we have shown in the work which factors are fundamental. The main component in the cost of cryptocurrency will be electricity, the cost of which is the most expensive in the developed countries of the world. You should not forget about the cost of the very expensive equipment for the extraction of cryptocurrency.